MENINGKATKAN KEMAMPUAN GURU KELAS MELAKSANAKAN PEMBELAJARAN PAKEM MELALUI KEGIATAN LESSON STUDY DI SD BINAAN KECAMATAN PASIR PENYU - Juliati Juliati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is motivated by the still weak ability of class teachers in carrying out classroom learning. The purpose of this research is to increase the ability of teachers to carry out classroom learning. The model used in this study is Lesson Study. This research was carried out in a built elementary school located in Pasir Penyu District. The design of this study uses school action research which consists of 2 cycles. The results of the research on the ability of teachers to carry out learning based on observations obtained an average score of 67 in the category C (Enough) / Not Completed in Cycles I and 73 were in category B (Good) / Completed in Cycle II. There was an increase in the average score by 6 points from Cycle I to Cycle II. With the results obtained, it can be said that with lesson study can improve the ability of teachers to carry out active, creative, effective, and enjoyable learning for the Elementary School teachers in Pasir Penyu District, Indragiri Hulu Regency.